(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
A pot experiment was carried out to evaluate the concentration and distribution of Lead, Cadmium and Nickel in industrial sludge. The test crop was Red Amaranth (Amaranthus gangeticus L.). Nitrogen was applied comprising the five combinations of different proportion of urea and industrial sludge and a control. Red Amaranth was harvested at 30 and 42 Days after sowing (DAS). Different physical and chemical analysis of soil, sludge, root, stem and leaf of the plant were carried out as required. Heavy metals concentration indicated the trends of Pb>Ni>Cd and distribution pattern of Pb, Cd and Ni were identified Leaf> root> stem, Root> leaf> stem and Root> leaf> stem respectively, both at 30 and 42 DAS with little exception. Industrial sludge had a significant influence on heavy metal concentration and distribution and contaminant food chain, although the data were below the maximum acceptable level. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15321 J. Asiat. Soc. Bangladesh, Sci. 38(1): 67-74, June 2012